COMUNICACIÓN Y EDUCACIÓN FINANCIERA: REFLEXIONES Y PRÁCTICAS ACADÉMICAS - Evelyn Iris Leite Morales Conde; Fábio Mamoré Conde (Universidade Federal de Rondônia, 2017)
In this work there are some bibliographical contributions and reflections on the subject of financial education from exploratory research developed in the project Communication and financial education: reflections and academic practices. It is the description of works with the planning, budgeting, consumption, consumer desires and instructions of the National Financial Education Strategy - NFES, proposed by the Department of Financial Education of the Central Bank of Brazil, and instituted by Decree No. 7,397, of December 22, 2010. Relevant literary support was observed that will support the second step of the research, characterized by Research-Action and production of radiophonic content with the themes addressed in classes Porto Velho city's elementary school, Rondônia state.